Appropriateness to set a group health based guidance value for T2 and HT2 toxin and its modified forms. (26th January 2017) - ,; Knutsen, Helle‐Katrine; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); et al.
Abstract: The EFSA Panel on Contaminants in the Food Chain (CONTAM) established a tolerable daily intake (TDI) for T2 and HT2 of 0.02 μg/kg body weight (bw) per day based on a new in vivo subchronic toxicity study in rats that confirmed that immune‐ and haematotoxicity are the critical effects of T2 and using a reduction in total leucocyte count as the critical endpoint. An acute reference dose (ARfD) of 0.3 μg for T2 and HT2/kg bw was established based on acute emetic events in mink. Modified forms of T2 and HT2 identified are phase I metabolites mainly formed through hydrolytic cleavage of one or more of the three ester groups of T2. Less prominent hydroxylation reactions occur predominantly at the side chain. Phase II metabolism involves conjugation with glucose, modified glucose, sulfate, feruloyl and acetyl groups. The few data on occurrence of modified forms indicate that grain products are their main source. The CONTAM Panel found it appropriate to establish a group TDI and a group ARfD for T2 and HT2 and its modified forms. Potency factors relative to T2 for the modified forms were used to account for differences in acute and chronic toxic potencies. It was assumed that conjugates (phase II metabolites of T2, HT2 and their phase I metabolites), which are not toxic per se, would be cleaved releasing their aglycones. These metabolites were assigned the relative potency factors (RPFs) of their respective aglycones. The RPFs assigned to the modified forms were all either 1 or less than 1. The uncertainties associated with the present assessment are considered as high. Using the established group, ARfD and TDI would overestimate any risk of modified T2 and HT2.